Career achievement after graduating from the Faculty of Music, UiTM / llham Khatijah Mohd Shaimy - Mohd Shaimy, llham Khatijah (2015)
This thesis is a study on career achievement after graduating from the Faculty of Music, UiTM, It investigates the factors that influence job opportunities for graduates from the faculty. The results of ‘he study will help students who are still studying at the Faculty of Music be better prepared for the world after graduation. The study offers recommendations based on the findings and hopes that the recommendations will further help enrich the local music industry. On top of that, we hope that the information provided in this thesis would contribute in improving and helping the student be better prepared for their future.